Anxiety Sensitivity and Panic Symptomatology: The Mediator Role of Hypochondriacal Concerns - Berrocal, Carmen; Ruiz Moreno, Francisca; Cano, Josefina (The Spanish Journal of Psychology, 2007)
The present study tests the mediating role of hypochondriasis to explain the relation between anxiety sensitivity and panic symptomatology. Fifty-seven outpatients with clinically significant levels of panic symptomatology were selected to participate in the study. Measures of anxiety sensitivity, hypochondriasis, and panic symptomatology were obtained from standardized, selfadministered questionnaires: the Anxiety Sensitivity Index (ASI; Reiss, Peterson, Gursky, & McNally, 1986), the Whiteley Index of Hypochondriasis (WI; Pilowsky, 1967), and the Panic- Agoraphobic Spectrum Self Report (PAS-SR; Cassano et al., 1997; Shear et al., 2001). Regression analyses were performed to test for the mediation models. The results show that the effect of anxiety sensitivity on panic symptomatology is not significant when controlling the hypochondriacal concerns, whereas the latter predicted panic symptoms. This result holds for the overall ASI as well as for the Physical Concerns and the Mental Incapacitation Concerns dimensions of the ASI scale. No evidence of a direct relation between the Social Concerns dimension and panic symptoms was found. The findings suggest that hypochondriacal concerns might represent the mechanism through which anxiety sensitivity is able to influence panic symptoms.
Keywords: Anxiety sensitivity; Hypochondriacal concerns; Panic-agoraphobic symptomatology; Mediators